South Africa's Health Promotion Levy: Excise tax findings and equity potential. (31st May 2021) - Hofman, Karen J.; Stacey, Nicholas; Swart, Elizabeth C.; Popkin, Barry M.; Ng, Shu Wen
Summary: In 2016, the South African government proposed a 20% sugar‐sweetened beverage (SSB) tax. Protracted consultations with beverage manufacturers and the sugar industry followed. This resulted in a lower sugar‐based beverage tax, the Health Promotion Levy (HPL), of approximately 10% coming into effect in April 2018. We provide a synthesis of findings until April 2021. Studies show that despite the lower rate, purchases of unhealthy SSBs and sugar intake consumption from SSBs fell. There were greater reductions in SSB purchases among both lower socioeconomic groups and in subpopulations with higher SSB consumption. These subpopulations bear larger burdens from obesity and related diseases, suggesting that this policy improves health equity. The current COVID‐19 pandemic has impacted food and nutritional security. Increased pandemic mortality among people with obesity, diabetes, and hypertension highlight the importance of intersectoral public health disease‐prevention policies like the HPL, which should be strengthened.